Radiation Sensing: Design and Deployment of Sensors and Detectors - Gamage, Kelum; Taylor, C. James (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Radiation detection is important in many fields, and it poses significant challenges for instrument designers. Radiation detection instruments, particularly for nuclear decommissioning and security applications, are required to operate in unknown environments and should detect and characterise radiation fields in real time. This book covers both theory and practice, and it solicits recent advances in radiation detection, with a particular focus on radiation detection instrument design, real-time data processing, radiation simulation and experimental work, robot design, control systems, task planning and radiation shielding.